Comparing CISNET Breast Cancer Incidence and Mortality Predictions to Observed Clinical Trial Results of Mammography Screening from Ages 40 to 49 - van den Broek, Jeroen J. (Med Decis Making, 2018)
BACKGROUND: The U.K. Age trial compared annual mammography screening of women ages 40 to 49 to no screening and found a statistically significant breast cancer mortality reduction at 10-year follow-up, but not at 17-year follow-up. The objective of this study was to compare the observed Age trial results to the Cancer Intervention and Surveillance Modeling Network (CISNET) breast cancer model predicted results. METHODS: Five established CISNET breast cancer models used data on population demographics, screening attendance, and mammography performance from the Age trial together with extant natural history parameters to project breast cancer incidence and mortality in the control and intervention arm of the trial. RESULTS: The models closely reproduced the effect of annual screening from ages 40 to 49 on breast cancer incidence. Restricted to breast cancer deaths originating from cancers diagnosed during the intervention phase, the models estimated an average 15% (range across models 13% to 17%) breast cancer mortality reduction at 10-year follow-up compared to 25% (95% CI 3% to 42%) observed in the trial. At 17-year follow-up, the models predicted 13% (range 10% to 17%) reduction in breast cancer mortality compared to the non-significant 12% (95% CI -4% to 26%) in the trial. CONCLUSIONS: Overall, the models captured the observed effect of screening from age 40 to 49 on breast cancer incidence and mortality in the U.K. Age trial, suggesting that the model structures, input parameters, and assumptions about breast cancer natural history are reasonable for estimating the impact of screening on mortality in this age group.